IMPLEMENTATION OF PTKIN QUALITY ANSURANCE: PERFORMANCE IMPROVEMENT EFFORTS THROUGH MOTIVATION AND JOB SATISFACTION IN ACEH - Yusaini Yusaini; Darmawati Darmawati; Mahyiddin Mahyiddin; Zainuddin Zainuddin (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This article discusses the quality assurance performance of the Aceh State Islamic Religious College (PTKIN), which is influenced by motivation and job satisfaction in the implementation of quality assurance. This article describes three important things, namely describing the response of quality assurance implementers on motivation and job satisfaction, and proving quantitatively about the contribution of both to the quality assurance performance of PTKIN Aceh. Obtaining data through a survey questionnaire on motivation, job satisfaction and performance. Data analysis used descriptive analysis techniques to explain motivation responses and job satisfaction. Testing the performance hypothesis of PTKIN Aceh quality assurance using a simple regression test. The results of the analysis concluded that the motivation and job satisfaction of the Aceh PTKIN quality assurance implementers in implementing the quality assurance system was Strong or Good, and had a significant positive effect on the motivation and job satisfaction variables on the performance of the Aceh PTKIN quality assurance implementers.